(untitled) (American & British Studies Annual, 2014)
This article compares the sorrowing child in Jonathan Safran Foer’s Extremely Loud and Incredibly Close (2005) and Brian Selznick’s The Invention of Hugo Cabret (2007), which break traditional novelistic frames through their use of visual material. Through their employment of the orphan figure and their inventive, experimental formal aspects, both Foer’s and Selznick’s novels work as interventions in the debate about the role of fiction after 9/11. Steering clear of a never-ending state of orphanhood, or a return to the nuclear family ideal of the 1950s, they Orfee different solutions to the family crisis triggered by the loss of a father in a burning building, and, by extension, to the national crisis triggered by 9/11. The bond between father and son that the novels portray represents an affective masculinity that is in line with the emotional narrative work that the two orphan boys perform in the plot and for the readers, which is similar to that of orphan girls in earlier American fiction. In addition to fulfilling the time-honored function of the orphan healing the adult world in a crisis-laden present, Foer’s Oskar and Selznick’s Hugo are post-9/11 “inventions” that highlight the uses of invention in a post-9/11 world.